Effect of Job Satisfaction, Supervision and Communication on Employee Performance at PT. Lautan Benua Nusantara Indonesia - Fanny Jovita; Cindy Erostya; Novita Dewi; Melkyory Andronicus (Journal of Business, Management, & Accounting, 2020)
The purpose of this study was to examine and analyze the effect of job satisfaction, supervision and communication on employee performance at PT. Lautan Benua Nusantara Indonesia. The population of this research is the employees of PT. Lautan Benua Nusantara Indonesia is 125 people. The research sample obtained 95 people with the Slovin formula and using the Simple Random Sampling Technique. The statistical methods used are validity and reliability tests and multiple linear regression analysis. The results showed that partially stated job satisfaction, supervision and communication had a significant effect on employee performance. Simultaneously stated that job satisfaction, supervision, and communication have a significant effect on employee performance